2008
DOI: 10.1176/appi.ps.59.5.507
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the New Users of Antipsychotic Medications?

Abstract: Objective-to examine changes in the prevalence of antipsychotic medication use and the characteristics of antipsychotic users in the US population.Methods-We use data from the Medical Expenditure Panel Survey from 1996/97 and 2004/05 to examine the rate of first and second-generation antipsychotic medication use and changes in the characteristics of users of all ages. We examine trends in the level of use by antipsychotic users both in terms of daily dose units and number of prescriptions.Results-The rate of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…Others have reported that increases in antipsychotic use have not corresponded with increases in daily doses. 12 Antipsychotic duration is not a measure of compliance or consumption. Finally, the lack of information on illness severity, treatment decisions, and clinical outcomes prohibits conclusions about the appropriateness of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that increases in antipsychotic use have not corresponded with increases in daily doses. 12 Antipsychotic duration is not a measure of compliance or consumption. Finally, the lack of information on illness severity, treatment decisions, and clinical outcomes prohibits conclusions about the appropriateness of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 Among youths with autism who were in foster care, 21% received Ն3 medications from different classes concomitantly for at least 30 days, compared with 10% among youths with autism and eligible for Medicaid through a disability status. 7 Finally, the increase has been primarily the second-generation antipsychotics (SGAs), [8][9][10][11][12][13][14] which carry a greater risk of metabolic adverse effects among children. 15 Concerning is the expanded use of antipsychotics for attention-deficit/hyperactivity disorder (ADHD) in the absence of schizophrenia, autism, or bipolar disorder for which these medications are typically prescribed.…”
mentioning
confidence: 99%
“…Nevertheless, increasing rates of antipsychotic treatment of young people 49 and common adverse metabolic effects 50 contribute to concerns over antipsychotic prescribing patterns to young people. 42,49,51 This study advances knowledge on the patterns of psychotropic medication use in a nationally representative sample of adolescents with well-characterized DSM-IV mental disorders and clinical correlates. Previous estimates of psychotropic medication use from pharmacy and insurance statistics are not based on representative samples of the population nor do they include comprehensive assessment of current mental disorders.…”
Section: Commentmentioning
confidence: 99%
“…The use of atypicals has accelerated rapidly since their introduction into the market. Domino and Swartz (Domino & Swartz, 2008) …”
Section: The Rise In the Use Of Atypical Antipsychoticsmentioning
confidence: 99%